Collective memory versus individual memory: on the question of the symphonic memory of the past - Myslivets, Nikolai L. (Journal of the Belarusian State University. Sociology, 2019)
The prerequisites for research interest increase in studying of memory of the past are pointed out in the introduction. Specific features of such forms of the representation of the past as history and memory are determined. The basic concepts used in the process of the supraindividual comprehension of the memory of the past are stated: they are generations’ experience, images of the past, historical memory, collective memory, individual memory. The main part of the article describes the essence and basic approaches for understanding of such forms of the past representation as collective and individual memory. It concludes the expediency of using the interdisciplinary approach for their study. The role of information channels as one of the most important sources of historical memory formation in modern society is stressed. The peculiarities of the evolution of collective and individual memory essence perceptions are studied. Various authors’ views on the nature and different forms of memory of the past essence are analyzed. The obtained results can be used in carrying out empirical research on the memory of the past in order to reveal the features of the intergenerational translation of the accumulated social and historical experience. The developed proposals can be used in practical activities to improve the system of ideological and educational work and the educational process content in educational institutions.
Keywords: the past; history; memory of the past; historical memory; collective memory; individual memory